The Effect of Health Promotion Through the YouTube Digital Platform on Adolescents’ Knowledge About Premenstrual Syndrome - Dini Afriani; Bambang Budi Rahardjo; Sukmayadi Sukmayadi; Gita Arisara; Anissa Nur Safitri (LP3M Universitas Muhammadiyah Tasikmalaya, 2026)
Premenstrual syndrome (PMS) is a common condition characterized by physical and emotional symptoms experienced by about adolescent girls before menstruation. Limited knowledge PMS may lead to inadequate awareness and poor management of symptoms. Digital platforms such as YouTube offer accessible and engaging media for health education among adolescents. This study aimed to determine the effect of health promotion delivered through the YouTube digital platform on adolescents’ knowledge about premenstrual syndrome (PMS) among students at MTS Al-Falaahiyyah, Ganeas District, Sumedang Regency, in 2025. This quantitative study employed a pre-experimental design with a one-group pre-test post-test approach. A total of 93 respondents were selected using total sampling. Data were collected using a structured knowledge questionnaire and analyzed using the Wilcoxon signed-rank test due to non-normal data distribution. The findings showed a significant increase in knowledge scores after the intervention. The mean pre-test score was 56.45, increasing to 88.01 in the post-test. Statistical analysis revealed a significant effect of YouTube-based health promotion on PMS knowledge (p-value = 0.000 < 0.05). Health promotion through the YouTube digital platform effectively increases adolescents’ knowledge about PMS. YouTube can serve as a recommended medium for reproductive health education in school settings.